Contribution to the knowledge of Acotylean Polyclads (Platyhelminthes, Polycladida) from Tunisian Coasts - Gammoudi, Mehrez; Tekaya, Saïda; Noreña, Carolina (Zootaxa, 2009)
Although the order Polycladida has been known from the Mediterranean basin since the XVIII century, many species have been described insufficiently and in some cases have been erroneously identified. A revision of the taxon Polycladida has been undertaken with the aim to contribute to the knowledge of Mediterranean polyclads. This first contribution deals with four species found on Tunisian coasts: Echinoplana celerrima Haswell, 1907; Leptoplana tremellaris (O. F. Müller, 1774) Oersted, 1843; Theama mediterranea Curini-Galletti, Campus & Delogu, 2008 and Imogine mediterranea (Galleni, 1976) Jennings & Newman 1996. Characters and diagnoses of the genus and species have been revised. Known and new internal and external morphological features have been added. Additionally, information about reproduction, distribution and habitat is provided.